Effect of different arginine methylations on the thermodynamics of tat peptide binding to HIV-1 TAR RNA - Kumar, Santosh; Maiti, Souvik (Biochimie, 2013)
RNA-binding proteins are an important class of mediators that regulate cell function and differentiation. Methylation of arginine, a post-translational modification (PTM) found in these proteins, can modulate their function. Arginine can be monomethylated or dimethylated, depending on the type of methyl transferases involved. This paper describes a comparative study of the thermodynamics of unmodified and modified Tat peptide interaction with TAR RNA, where the peptide is methylated at epsilon (epsilon) and eta (eta) nitrogen atoms of guanidinium group of arginine side chain at position 52 or 53. The results indicate that monomethylation of arginine at epsilon (epsilon) nitrogen atom enhances binding affinity, owing to a more favourable enthalpy component which overrides the less favourable entropy change. In contrast, monomethylation of arginine residue at eta nitrogen results in reduced binding affinity originating exclusively from a less favourable enthalpy change leaving entropic component unaffected. However, in case of simultaneous methylation at epsilon and eta positions, the binding parameters remain almost unaffected, when compared to the unmodified peptide. In case of symmetric dimethylation at eta position the observed enthalpy change of the binding was found to be smaller than the values obtained for the unmodified peptide. Asymmetric dimethylation at eta position showed the most reduced binding affinities owing to less favourable enthalpy changes. These results provide insights that enable elucidation of the biological outcome of arginine methylation as PTMs that regulate protein function, and will contribute to our understanding of how these PTMs are established in vitro and in vivo. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: HIV-1; Post-translational modification; Protein methylation; RNA-protein interaction; Thermodynamics

Conserved RNA binding activity of phosphatidyl inositol 5-phosphate 4-kinase (PIP4K2A) - Behari, Jatin; Borkar, Pranita; Vindu, Arya; Dandewad, Vishal; Upadrasta, Sindhuri; Shanmugam, Dhanasekaran; Seshadri, Vasudevan (Frontiers in Molecular Biosciences, 2021)
Plasmodium falciparum is a causative agent for malaria and has a complex life cycle in human and mosquito hosts. During its life cycle, the malarial parasite Plasmodium goes through different asexual and sexual stages, in humans and mosquitoes. Expression of stage-specific proteins is important for successful completion of its life cycle and requires tight gene regulation. In the case of Plasmodium, due to relative paucity of the transcription factors, it is postulated that posttranscriptional regulation plays an important role in stage-specific gene expression. Translation repression of specific set of mRNA has been reported in gametocyte stages of the parasite. A conserved element present in the 3 ` UTR of some of these transcripts was identified. Phosphatidylinositol 5-phosphate 4-kinase (PIP4K2A) was identified as the protein that associates with these RNA. We now show that the RNA binding activity of PIP4K2A is independent of its kinase activity. We also observe that PIP4K2A is imported into the parasite from the host on Plasmodium berghei and Toxoplasma gondii. The RNA binding activity of PIP4K2A seems to be conserved across species from Drosophila and C. elegans to humans, suggesting that the RNA binding activity of PIP4K may be important, and there may be host transcripts that may be regulated by PIP4K2A. These results identify a novel RNA binding role for PIP4K2A that may not only play a role in Plasmodium propagation but may also function in regulating gene expression in multicellular organisms.
Keywords: malaria; posttranscriptional gene regulation; RNA-protein interaction; translation regulation